Quality of life in adult patients with congenital heart disease: Results of a double-center study - Khajali, Zahra; Sayyadi, Amin; Ansari, Zahra; Aliramezany, Maryam (Frontiers in Psychiatry, 2023)
Prevalence of Congenital heart disease has increased in recent years and they all have to deal with sequelae of the multiple medical and surgical treatments that can affect different aspects of their life which could be reflected in their quality of life. In Iran, to best our knowledge quality of life of adult patients with congenital heart disease has not been investigated. this study aimed to investigate the quality-of-life of adult patients with congenital heart diseases. In 2022 a two-center study was designed on adult patients with congenital heart disease receiving out-patient care in Kerman Besat clinic and Rajaee hospital clinic in Tehran, Iran. Inclusion criteria were documented diagnosis of congenital heart disease based on guidelines, ejection fraction of above 45% and age of 18-55 years. We used simple random sampling method and the sample consisted of 120 individuals. At the day of referring to adult congenital heart diseases clinics, we asked patients to fill in questionnaires after ensuring their written consent to participate in the study. Data were analyzed via SPSS-22 using chi square. A total of 101 adults with a mean age of 31.05 years participated in the study. Demographic and socio-economic factors had no significant relationship with the patients' quality of life. But factors related to the disease had an effect. Adults with congenital heart disease had a low quality of life, which has nothing to do with their demographic and socio-economic factors. That is, the existence of the disease alone and its accompanying complications can affect the quality of life of these people. Hence, mental health of adult patients with congenital heart disease should be monitored in addition to their routine cardiac care.